Electronic-Based Traffic Law Enforcement by the Surabaya Police Traffic Unit to Reduce the Number of Traffic Violations - Xavier, Fransisca Zelia Woda (Advances in Police Science Research Journal, 2024)
The population density of Surabaya City is proportional alongside the citizen’s activity of transportation usage or road users. This results in escalation of road congestion and traffic violation. The Electronic Traffic Law Enforcement (ETLE). Which has been established nationally since 2021, excelled in reducing traffic violation in the Surabaya Citypolice jurisdiction. accordance with the chief of National Police priority program number 4 regarding the improvement of law enforcement performance, it is expected that ETLE is able to carry out alterations for modern policing. The aim of this research is to inquire the model of electronic- based traffic law enforcement by the Surabaya Police traffic unit and the urgency of the occuring law amendments. This research utilizes qualitative method which mainly focuses on the electronic-based law enforcement against traffic violators. Data colecction techniques conducted throughout the reasearch are interview, observation, and document study. This paper conducted in order to obtain results regarding the model of electronic based traffic law enforcement by the Surabaya Police Traffic unit which is applied by Soerjono Soekanto’s law enforcement factors and identified the presence of influence and intricacies in facing electronic based traffic law enforcement. Meanwhile, the writer managed to identify the urgency within the motive of implementing electronic-based law enforcement amid the law reformation. It includes legal culture structure reform, legal substance reform, and legal culture reform. Hence, it needs the partnership with the government concerning CSR fund to increase statis ETLE in Surabaya and along with the upsurge of dissemination through social media are required.